The potential of bilateral migration agreements: From symbolic politics to practical implementation - Nadine Biehler; David Kipp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2024)
Migration cooperation with third countries is thriving. Bilateral agreements with countries of origin, host countries and transit countries are increasingly seen as important instruments for overcoming the challenges associated with immigration. With the Special Commissioner for Migration Agreements, the German government has created a focal point to bring together the political objectives in the areas of return and labour recruitment into one comprehensive approach. Initial agreements were quickly reached in the hope of sending a clear signal to the electorate. Beyond their symbolic effect, the agreements have the potential not only to be the starting point for long-term, sustainable migration policy cooperation, but also to contribute towards the development of the countries of origin. In order to realise this potential, a better reconciliation of interests between the respective partner countries and Germany, capacity building in the area of recruitment and more consistency in external migration policy are required.
Keywords: 320; migration cooperation with third countries; countries of origin; host countries; transit countries; labour recruitment; Special Commissioner for Migration Agreements